Galvanic Tongue Stimulation Inhibits Five Basic Tastes Induced by Aqueous Electrolyte Solutions - Aoyama, Kazuma; Sakurai, Kenta; Sakurai, Satoru; Mizukami, Makoto; Maeda, Taro; Ando, Hideyuki (Frontiers in Psychology, 2017)
Galvanic tongue stimulation (GTS) modulates taste sensation. However, the effect of GTS is contingent on the electrode polarity in the proximity of the tongue. If an anodal electrode is attached in the proximity of the tongue, an electrical or metallic taste is elicited. On the other hand, if only cathodal electrode is attached in the proximity of the tongue, the salty taste, which is induced by electrolyte materials, is inhibited. The mechanism of this taste inhibition is not adequately understood. In this study, we aim to demonstrate that the inhibition is cause by ions, which elicit taste and which migrate from the taste sensors on the tongue by GTS. We verified the inhibitory effect of GTS on all five basic tastes induced by electrolyte materials. This technology is effective for virtual reality systems and interfaces to support dietary restrictions. Our findings demonstrate that cathodal-GTS inhibits all the five basic tastes. The results also support our hypothesis that the effects of cathodal-GTS are caused by migrating tasting ions in the mouth.